Identification of Novel Drug Targets and Potential Antibacterial Traditional Chinese Medicine Compounds for Klebsiella pneumoniae through in silico and Antibacterial Activity Evaluation - Li, Yanping; Kumar, Suresh; Peng, Hao; Zhang, Lihu (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Klebsiella pneumoniae is a ubiquitous opportunistic pathogen that poses a significant threat to hospitalized patients by causing a wide range of infections. The alarming increase in clinical resistance to all current antibiotics necessitates the urgent identification of novel therapeutic targets and development of effective antimicrobial agents. Materials and Methods Using pan-genomic analysis of the core protein repertoire of K. pneumoniae, we applied a subtractive proteomics approach to uncover potential drug targets. This has led to the identification of CsgD as a promising candidate. Structural modelling and validation of CsgD were performed. A comprehensive virtual screening of 29,384 natural compounds sourced from Traditional Chinese Medicine (TCM) libraries was performed against CsgD, which yielded three candidates with low binding energies and desirable pharmacodynamic profiles, as validated by Absorption, Distribution, Metabolism, Excretion, and Toxicity (ADMET) prediction.100-nanosecond molecular dynamics simulations were performed to further substantiate their efficacy. Results Through a rigorous virtual screening process using the TCM database, we identified three compounds with potential antibacterial activity against K. pneumoniae. In particular, mydriatin stands out as a potent CsgD inhibitor, demonstrating a significant inhibitory effect on antibiotic-resistant strains of K. pneumoniae in vitro antibacterial activity evaluation. Conclusion This study identified mydriatin as a potential therapeutic agent targeting CsgD in K. pneumoniae, offering a promising strategy for the development of novel antimicrobials to combat drug-resistant infections caused by this pathogen. Our results highlight the importance of using natural product libraries and computational methods in the discovery and rational design of novel antibiotics to address the pressing challenges posed by multidrug resistance in K. pneumoniae.
Keywords: In vitro evaluation; Klebsiella pneumoniae; Molecular docking; Molecular dynamics simulation; Subtractive proteomics; Virtual screening